How useful is the concept of polycrisis? Lessons from the Development of the Canada Emergency Response Benefit during the COVID-19 pandemic - Shannon Dinan; Daniel Béland; Michael Howlett (Policy Design and Practice)
The empirical basis for the concept of polycrisis has only been articulated at a high level of abstraction, typically dealing with global issues like climate change or migration. Because of that, its relevance and utility at the domestic level vis-à-vis adding value to existing studies of crisis management are unclear. As a set of events lasting over two years involving a pandemic with multiple simultaneous and interconnected economic and public health implications, the COVID-19 pandemic provides both scholars and practitioners with a rare opportunity to look in more detail into how domestic policy design actually occurred during this global event. In this article, we investigate the creation of the Canada Emergency Response Benefit (CERB) program during the COVID-19 crisis. The CERB case illustrates the importance of three factors that together form a trifecta of best practices for national-level policy design in a crisis—policy integration, learning, and agility—and shows how these elements evade capture by the polycrisis concept, thereby limiting its usefulness.